ANALISIS KESESUAIAN LAHAN UNTUK PENGEMBANGAN KAKAO BERDASARKAN APLIKASI SPKL (SISTEM PENILAIAN KESESUAIAN LAHAN) DI KABUPATEN BANTAENG: Land Suitability Analysis For Cocoa Development Based On SPKL Application (Land Suitability Assessment System) In Bantaeng Regency - Nirmala Juita; Husnul Mubarak; Erwin Wijaya; Emmy Fadhila; Nurmaranti Alim (Universitas Hasanuddin, 2021)
Cocoa is one of the plantation commodities that has an important role in economic activities in Indonesia. Cocoa can also be used as an alternative source of biohydrogen energy and is very beneficial for health such as reducing the risk of heart attack and stroke, reducing symptoms of depression, lowering blood pressure, maintaining healthy teeth and bones and protecting the body from cancer. The method used in this research is the SPKL application (version 2.0). The results obtained from this study are S3 (marginally appropriate) at the observation points of soil profiles 1 and 4, while the land suitability class N (not suitable) is found in profiles 2, 3 and 5. Limiting factors such as annual temperature, slope, soil depth and coarse fragments, is a limiting factor that is difficult to repair, while soil chemical properties such as K2O can be overcome by fertilization.